Trinidad and Tobago : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper analyzes the energy sector and labor market developments in Trinidad and Tobago. It discusses monetary and exchange rate policy and describes the institutional setting and economic structure within which monetary and exchange rate policy is conducted. The framework under which monetary policy is formulated and implemented is outlined. The paper also reviews the evolution of monetary and exchange rate policies, and presents some comments on the effectiveness of monetary and exchange rate policy.